2019
DOI: 10.21203/rs.2.13765/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The association of circulating irisin with metabolic risk factors in Chinese adults: a cross-sectional community-based study

Abstract: Background

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…In addition, it was shown that the serum irisin concentrations of individuals in the group with a diagnosis of MetS were higher compared to control group; this is attributed to the increased irisin resistance in adipose tissue (31). In the study of Tang et al, (16) a positive relationship was found between irisin and triglycerides; however, no relationship was found between total cholesterol and HDL-C and irisin.…”
Section: Irisinandmetabolic Syndromementioning
confidence: 84%
See 4 more Smart Citations
“…In addition, it was shown that the serum irisin concentrations of individuals in the group with a diagnosis of MetS were higher compared to control group; this is attributed to the increased irisin resistance in adipose tissue (31). In the study of Tang et al, (16) a positive relationship was found between irisin and triglycerides; however, no relationship was found between total cholesterol and HDL-C and irisin.…”
Section: Irisinandmetabolic Syndromementioning
confidence: 84%
“…In studies conducted on individuals with T2DM (37) and gestational Diabetes Mellitus (38), it has been shown that serum irisin concentration was inversely related to the development of diabetes, considering that impairment of PGC-1α expression may result in this in individuals with T2DM. Fasting insulin, HOMA-IR were inversely associated with irisin concentration (16,39). Shoukry et al, (40) has found that serum irisin concentration was lower among individuals with new onset T2DM compared to healthy counterparts.…”
Section: Irisinandinsulin Resistancementioning
confidence: 97%
See 3 more Smart Citations